Syntheses and Molecular Structures of Liquid Pyrophoric Hydridosilanes. Issue 7 (27th July 2020) - Gerwig, Maik; Böhme, Uwe; Friebel, Mike; Gründler, Franziska; Franze, Georg; Rosenkranz, Marco; Schmidt, Horst; Kroke, Edwin
Abstract: Trisilane, isotetrasilane, neopentasilane, and cyclohexasilane have been prepared in gram scale. In‐situ cryo crystallization of these pyrophoric liquids in sealed capillaries on the diffractometer allows access to the single crystal structures of these compounds. Structural parameters are discussed and compared to gas‐phase electron diffraction structures from literature and with the results from quantum chemical calculations. Significantly higher packing indices are found for the silanes compared to the corresponding alkanes. Radiation with ultraviolet light (365 nm) and parallel ESR (EPR) measurement shows that cyclohexasilane is easily split into radicals, which subsequently leads to the formation of branched and chain‐like oligomers. The other compounds form no radicals under these conditions. NMR spectra of all four compounds have been recorded. Abstract : Light it up : In‐situ cryo crystallization and structure analysis reveal the solid‐state structures of several pyrophoric hydridosilanes.